The Impact of the Ownership Structure of the Company Managing an Airport on its Functioning (Contemporary Central & East European Law, 2020)
This article tackles the problem of the ownership structure of the enterprises managing airports. The process of privatization of certain airports that has recently been conducted in France provoked a discussion about the possible effects of this process. The critical report of the Court of Auditors (Cour des Comptes), published after the privatization of the airports in Toulouse, Nice and Lyon, as well as the strong opposition to the privatization of Group ADP (managing the airports in Paris), leads to the conclusion that it is necessary to verify if the legal measures adopted in European Union’s and national legal systems are efficient and adequate to ensure the proper functioning of airports after privatization.